2022
DOI: 10.3389/fnut.2021.806744
|View full text |Cite|
|
Sign up to set email alerts
|

1H NMR-Based Chemometrics to Gain Insights Into the Bran of Radiation-Induced Colored Wheat Mutant

Abstract: Recently, wheat has attracted attention as a functional food, rather than a simple dietary energy source. Accordingly, whole-grain intake increases with an understanding of bioactive phytochemicals in bran. The development of colored wheat has drawn more attention to the value of bran owing to its nutritional quality, as well as the antioxidant properties of the colorant. The present 1H NMR-based chemometric study evaluated the compositional improvement of radiation-induced mutants in purple wheat by focusing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 58 publications
(102 reference statements)
2
14
0
Order By: Relevance
“…The previous investigation revealed that the non-irradiated colored wheat PWB is an improved variety in terms of higher contents of the primary metabolites compared with those of other varieties. 22 Consistent with the previous observation, the present non-targeted PCA analysis placed PWB at the edges of the negative side of PC1. Moreover, the bins numbered higher than 60 (bins 60−232, "≥ bin60" for δ H 0.50− 7.64 ppm), which were attributed to the primary metabolites identified in the previous study, were placed on the same side (Figure S1, Supporting Information).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The previous investigation revealed that the non-irradiated colored wheat PWB is an improved variety in terms of higher contents of the primary metabolites compared with those of other varieties. 22 Consistent with the previous observation, the present non-targeted PCA analysis placed PWB at the edges of the negative side of PC1. Moreover, the bins numbered higher than 60 (bins 60−232, "≥ bin60" for δ H 0.50− 7.64 ppm), which were attributed to the primary metabolites identified in the previous study, were placed on the same side (Figure S1, Supporting Information).…”
Section: Resultssupporting
confidence: 92%
“…The 40 wheat bran samples were previously evaluated by targeted 1 H NMR-based analysis focusing on 33 defined metabolites. 22 In ), while no corresponding observation was in the original purple wheat bran (PWB) (Figure 1). This finding motivated further statistical analysis; thus, a spectral binning process was conducted.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations